EXTRACTION OF RARE EARTH METALS FROM MONAZITE MINERAL USING ACID METHOD - Isyatun Rodliyah; Siti Rochani; Tatang Wahyudi (Puslitbang tekMIRA, 2015)
There are two types of REE-bearing mineral in Indonesia, namely monazite and xenotime. Those minerals have not been further processed to obtain pure REEs or to obtain its oxides. The objective of this study is to study the performances of the REE extracted from monazite in acid method. The results show that the highest REE-extraction (28.41%) is achieved when the comparison between of sulfuric acid and water (v/v) is 1:2 with leaching temperature 220°C and leaching time 150 minutes. The process employed hydrogen peroxide as an oxidizer. Pregnant solution was then precipitated using sodium hydroxide and then was calcined at 900°C for 3 hours to produce RE-oxide. Characteristic of the RE-oxide contains such elements of Ce, Gd, Y, Nd, La, Dy and Sm within 29.10, 1.54, 1.53, 11.53, 14.02, 0.489 and 1.85%, respectively.